Pengaruh Model Pembelajaran Children Learning In Science (CLIS) Berbantu Media Audio Visual - Bayu Widiyanto; Muhammad Abdul Halim Sidiq; Mohammad Darwis (Lembaga Penelitian, Penerbitan dan Pengabdian Masyarakat - Islamic Institute of Syarifuddin Lumajang, Indonesia., 2021)
IPA was natural science and the structured material which arranged based on the observation. Therefore, it needed the appropriate learning model and medium in which the students could be helped in mastering the learning courses and examining the students to develop their ideas or opinion about a certain problems in learning, also reconstruct their ideas or opinion based on the observation or experiment. The model learning of children learning in science (CLIS) could assisted and developed scientific approach, and also it could found and solved new problems through science method. The research aimed to know the influence learning model of children learning in science (CLIS) using the audio visual toward the science result of study at Elementary School. The subject of research were the IV class of SDN Kemuning Lor 02. The research method was pre-experiment through designed group; pre-test and post-test. Based on the research result showed that t counted 6,810 (df29) > t tabel 1,699 (df29) and value sig. (2-tailed) 0,000 < 0,005 so that the were significant influence on the implementing the model of learning CLIS assisted audio visula toward the result of IPA study in Elementary School